Efficacy Muscle Energy Technique for Low Back Pain - Achmad Fariz; Rachma Putri Kasimbara; Sartoyo Sartoyo (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Background: Low back pain is one of the common musculoskeletal disorders. Muscle energy technique (MET) may be a useful intervention for treating such disorder. Objective: The aim of this study was to compare the effect of MET in people with mechanical back pain. Methods: A randomized controlled trial was undertaken. thirty patients with mechanical back pain were randomly allocated to either the MET group or control group. The former group received MET pre-post 3 and 6 times, and the latter group MET pre-post 6 and 12 times treatment. Treatment was given once a day for 30 days. A numerical pain rating scale (NPRS) was used to measure the intensity of pain was immediately before treatment and again on the 3th, 6th and 12th day. Results: NPRS scores showed no significant improvement in MET 3th and 6hh time and MET groups on the 6th and 12th day post intervention (p <0.05). However, NPRS scores showed better improvement in the MET group A as compared to the MET group B (p < 0.015). Conclusion: Muscle energy technique was better in improving pain in people with mechanical back pain.